Matcha Tea: Analysis of Nutritional Composition, Phenolics and Antioxidant Activity - Koláčková, Tereza; Kolofiková, Kateřina; Sytařová, Irena; Snopek, Lukáš; Sumczynski, Daniela; Orsavová, Jana (Plant foods for human nutrition, 2020)
Matcha was analysed for its chemical composition, fibre, vitamin C, caffeine and chlorophyll contents. Flavonoids and phenolics, phenolic profiles and antioxidant activity both in water and methanol solutions were determined. In vitro digestibility was established. To understand the contribution of individual substances to antioxidant activity or digestibility their mutual correlations were evaluated. Crude fibre (10.7-17.5%), neutral-detergent fibre (30.7-42.8%) and organic matter digestibility values (59.4-69.7%) showed positive correlations, in contrast to protein contents (20.3-35.0%). It seems that chlorophyll b was a stronger contributor to antioxidant activity than chlorophyll a. The highest contents of flavonoids (99-139 mg RE/g) and phenolics (169-273 mg GAE/g) were determined in methanol fractions. High concentrations of chlorogenic (up to 4800 μg/g), sinapic (up to 1400 μg/g) and gallic acids (up to 423 μg/g) were recorded. Kaempferol and rutin were not proved as significant contributors to antioxidant activity.
Keywords: flavonoidy; Phenols; čaj; Chlorophyll A; Flavonoids; antioxidancia; Plant Extracts; Tea; fenoly; chlorofyl a; Antioxidants; rostlinné extrakty